Landscape change in the Ifugao Rice Terraces, Philippines with the advent of modern agricultural technologies - Gomez, Romeo A.; Pacardo, Enrique P. (2005)
Recent agricultural technology introductions in the rice terraced landscape in the Province of Ifugao have apparently altered the native setting in the country's only "living cultural landscape" under the UNESCO World Heritage List. This landscape, which has traditionally been an ecosystem where indigenous culture and environment are closely enmeshed into the rubrics of harmonious co-existence and co-adaptation for several centuries, showcases a sustainable production system centered on native rice. Quite recently, however, it has seemingly shown signs of environmental degradation. The changing agricultural landscape, driven by biophysical, socio-economic, and institutional factors, has consequently led to the disruption of the ecological functions/services in the area, as evidenced by observed and perceived perturbations in the various bio-physical and socio-cultural dimensions-- indigenous agricultural practices, soil fertility and productivity, ecological balance food (traditional rice) sufficiency, and aesthetic value of the eco-tourism site.
Keywords: Ifugao rice terraces; Agricultural technologies